ANALISIS EFEKTIVITAS PENGELOLAAN MODAL KERJA DALAM RANGKA MENINGKATKAN PROFITABILITAS PADA KOPERASI SERBA USAHA REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Nadila Rahmadani; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effectiveness of working capital management in increasing profitability in the Rejosari Multipurpose Cooperative, Tenayan Raya District, Pekanbaru City. The data used is secondary data, namely financial statements in 2016 - 2020. This study uses quantitative data analysis using a descriptive approach. The analysis used is liquidity ratio, profitability ratio and activity ratio.The results of the analysis showed that the effectiveness of working capital management in order to increase profitability in the Cooperative Of All-Business Rejosari Kecematan Tenayan Raya Kota Pekanbaru for the last five years is said to be ineffective because there is still a fluctuating ratio. This can disrupt the operation of the cooperative so that it can affect the development of the cooperative. Judging from the results of liquidity ratio analysis, in general the criteria are not good. The results of profitability ratios, in general this ratio shows that the use of assets in generating profits is good and the activity ratio, in general fluctuating, so that working capital turnover, total assets and receivables are still running well with ineffective criteria, as well as the existence of several policy explanations of the existing problems in the Cooperative All-Business Rejosari Kecematan Tenayan Raya Kota Pekanbaru regarding receivables, cash and supplies in order to manage to be effective. Keywords: Efectiveness, Working Capital, Liquidity, Profitability. Activity